Insight into the minds of tweens: unlocking the mystery of cool brands / Masdiana Sulaiman - Sulaiman, Masdiana (Institute of Graduate Studies, UiTM, 2016)
This study examines how tweens define cool and why cool brands are important to them. Tweens are essentially the segment between childhood and adolescence or the younger end of the teenagers’ age spectrum and this market is deemed important as their consumption power increases with the growing buying power of consumers specifically in Malaysia. Understanding the definition of cool is important to marketers, but a clear definition of the cool concept has been under-theorized in the field of marketing, psychology or even sociology, particularly with a focus on tweens. To close this gap, this study focuses on how tweens perceived the concept of cool, the importance of the cool notion to them and how this is likely to influence their brand choices. Using the qualitative approach based on the interpretive paradigm with an emic focus, a semi structured interview guide was utilised for the face-to-face interview sessions and through in depth narrative analysis, this study theorizes the cool notion from the perspectives of the tweens who were selected specifically from five primary schools and three secondary schools in Kuala Lumpur, Malaysia…